IMPLEMENTASI ASWAJA DALAM PERSPEKTIF NU DI TENGAH KEHIDUPAN MASYARAKAT - Qomar, Mujamil (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Ahlussunnah wal Jamaah (Aswaja) is a theological sect who claimed by various Islamic organization in both redactional and substantive. Some of them is Laskar Jihad Ahlussunnah wal Â Jamaah, Nahdlatul Ulama, Muhammadiyah, Persatuan Islam and Wahabi. But of all the organization doesnât have the same attitude, thingking, response to a tradition (culture) and political view. Aswaja among the public and ulama still partically understood, local and organizational ideology tendentious. The emergence of Aswaja is reaction to the Mutazilah were less strong in holding the sunnah of the Prophet rather than else, so it appears as an antithesis to Hegelian dialectic perspective. Aswajaâs doctrine is constructed by al-Asyari and al-Maturidi, but both have different patterns of thought: al-Asyariâs thought is more traditional whereas al-Maturidi is rational. Aswajaâs doctrine version of al-Asyari, in practically followed by NU. The fikih sect follow Imam Syafii and Sufism follow Imam Junaid al-Baghdadi or Imam al-Ghazali. All they thoughts represented moderate character, so NU is a moderate Islamic organization. But NU becomes less interesting now. Therefore NU need to reconstruction four actions related to both management and organizational leadership, role model of society and state, human resources in a expertise variety and strategic forces in contemporary society.Keywords: Aswaja, NU, Society